‘My identity as a foreigner in Jyväskylä’, shared by seven immigrant women. - Solidaki, Ilektra (2018)
Finland is a society which has gradually and recently turned its homogeneous character of country towards a multicultural one. Thus, while the migration rates show upward trends, challenges constantly pressure the society on how to embody the new populations and this alone can hinder a number of personal struggles when referring to the foreigner perception of reality which is closely connected with the society itself. Through integration and while existing among cultural worlds, the cultural identity of a foreigner is constantly on shape and using multiculturalism as a vehicle of performance, it interrelates with the society. The aspiration of this research was to examine the socio – cultural perceptions of seven foreigner individuals residing in Jyväskylä, Finland. This qualitative study has as objective to contribute a closer insight of how a vivid, self-appointed, multicultural society adjusts the foreigner through integration processes, concerning their perception. The main research question is based on the socio – cultural perceptions of foreigner individuals in this society. To answer my main question and others that arise, I draw on theoretical insights from migration, multiculturalism, cultural identity, integration and hybridity books, published reports, policies, and articles akin with each area of investigation. The scrutiny and discussion of my conclusions signify that the Finnish society has given and keeps giving keen interest on the ‘two-way process’ character of integration, while the individual perception is fluctuating among cultural worlds. As a result of all this process and with the help of in-depth interviews with open ended questions, the sample admits that does not feel marginalized in society. On the contrary, they feel safe and accepted on a broad level but they do feel excluded in life practicalities and that is mainly because of the lack of language skills that can assist them in entering professional fields or making deeper friendships. This alone seems to affect the sense of belonging an individual feels in the society.